The Noli Me Tangere Novel: An Instructional Model for Teaching - Mabalhin, Joel Q. (Selected Topics in Humanities and Social Sciences Vol. 4, 2021)
This study covers the analysis of selected utterances from selected 25 chapters of Noli Me Tangere novel of Dr. Jose P. Rizal through semantic and pragmatic views. The researcher analyzed the whole book and look for the difficult utterances in every chapter. It should pass through three stages. First is focusing on the analysis of the utterances based on linguistic-semantic interpretation. Second is through pragmatic, which actually based on two important contexts; the linguistic and physical contexts. And the third stage is to identify the relationship of the interpretation between semantic and pragmatic views. Validators were given copies of the analysis to double-check and recommend some modifications of the interpretation. After which, the researcher, make an instructional model for reading using the different strategies in teaching.